What clinical factors are associated with mortality in septicemic melioidosis? A report from an endemic area - Pornanan Domthong; Seksan Chaisuksant; Kittisak Sawanyawisuth (Journal of Infection in Developing Countries)
Introduction: Melioidosis, caused by Burkholderia pseudomallei, has high mortality, particularly in its septicemic form. Data on the factors associated with mortality from melioidosis are still limited. Methodology: All patients (≥ 15 years of age) who were positive for melioidosis by blood culture in the year 2009 were enrolled. The study was conducted at Khon Kaen Hospital, Thailand. Patients were divided into two groups: surviving and deceased. Multivariate logistic regression was used to identify factors associated with death by three models: clinical, laboratory, and combined. Results: There were 97 patients who had blood cultures positive for melioidosis. The mortality rate was 54.17% (52 patients). The clinical presentation model found one significant factor associated with mortality from septicemic melioidosis: pulmonary presentation. Two factors were statistically significant for death as determined by the laboratory model: white blood cell count (WBC) and blood urea nitrogen (BUN) value. For the combined model, three significant factors were associated with death: pulmonary presentation, WBC, and BUN. The adjusted odds ratios (95% confidence interval) of the three factors were 10.739 (3.300–34.953), 0.930 (0.877–0.985), and 1.057 (1.028–1.087), respectively. Conclusions: Three clinical factors associated with mortality in septicemic melioidosis were pulmonary presentation, white blood cell count, and blood urea nitrogen level. Physicians should be aware of high mortality if septicemic melioidosis patients have these clinical features. Aggressive treatment may be needed.